Exploring Self-Efficacy of Early Childhood Education Teachers in Teaching English to Young Learners in Indonesian Kindergartens: A Mixed-Methods Approach - Alfu Nikmah; Pasiningsih Pasiningsih; Narendra Adhitya Majid; Nisa Nabila; Intan Nadiastuti (Prominent, 2025)
This study is aimed to analyze early childhood education (ECE) teachers’ self-efficacy in teaching English for young learners in kindergarten context. The mixed method was chosen as the research design to answer the research question to what extent do ECE teachers believe in their ability to teach English to young learners seen from three dimensions of self-efficacy, magnitude, generality, and strength. The participants in this study were ten kindergarten teachers in a school located in Central Java. In collecting the data, they were given a questionnaire adopted from Bandura’s theory that proposes the level of self-efficacy containing three dimensions, magnitude dimension, generality dimension and strength dimension. Then, an in-depth interview was conducted to validate and gather more data from the questionnaire filled in by participants. Findings showed that the level of self-efficacy of teachers was adequate in the three dimensions of self-efficacy, magnitude (score 3), generality (score 3), and strength (score 3). However, participants showed lack of self-efficacy in the two statements in strength dimension, feeling comfortable to help their students learning English and teaching English is not frustrating. On going professional developments are needed, such as regular workshop and English proficiency test for teachers to improve ECE teachers’ self-efficacy in teaching English for young learners.